2007
DOI: 10.1088/0957-4484/18/49/495707
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical investigation of defects in a boron nitride monolayer

Abstract: We have investigated, using first-principles calculations, the energetic stability and structural properties of antisites, vacancies and substitutional carbon defects in a boron nitride monolayer. We have found that the incorporation of a carbon atom substituting for one boron atom, in an N-rich growth condition, or a nitrogen atom, in a B-rich medium, lowers the formation energy, as compared to antisites and vacancy defects. We also verify that defects, inducing an excess of nitrogen or boron, such as N(B) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
87
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(105 citation statements)
references
References 26 publications
16
87
1
1
Order By: Relevance
“…The comparative analysis of structures with defects was always carried out relatively to an ideal (non-defective) layer. Similar to previous calculations for an h-BN layer [21], the investigated model systems have either an N or an Al-rich environment, depending on the atomic reservoir specifically employed. The usual phase of constituent Nitrogen is gaseous (chemical potential μ N ) while the usual phase for constituent Al is solid (chemical potential for FCC Al μ Al ).…”
Section: Computational Detailsmentioning
confidence: 96%
“…The comparative analysis of structures with defects was always carried out relatively to an ideal (non-defective) layer. Similar to previous calculations for an h-BN layer [21], the investigated model systems have either an N or an Al-rich environment, depending on the atomic reservoir specifically employed. The usual phase of constituent Nitrogen is gaseous (chemical potential μ N ) while the usual phase for constituent Al is solid (chemical potential for FCC Al μ Al ).…”
Section: Computational Detailsmentioning
confidence: 96%
“…SW defects may also appear under large tension, as simulations 493 indicate. Thus the properties of point defects in BN nanosystems have been studied in a considerable body of theoretical papers 212,[494][495][496][497][498][499][500] within the framework of DFT.…”
Section: Theory Of Point Defects In Bn Nanotubesmentioning
confidence: 99%
“…Supporting this observation, theoretical calculations predict a higher formation energy for B monovacancies compared to N. 48,49 In contrast, high-resolution transmission electron microscopy (HRTEM) studies have reported recently the formation of point defects in h-BN single-layers, thinned down with a high-energy electron beam. 29,30,50,51 Strikingly, it seems that B vacancies are preferentially formed to N vacancies.…”
Section: Introductionmentioning
confidence: 99%